Cultural Considerations in Palliative Care Provision: A Scoping Review of Canadian Literature - Erynn M. Monette (Palliative Medicine Reports, 2021)
Background: Palliative care, a division of health care that provides treatment to patients facing terminal or incurable illness, prioritizes maintaining quality of life for the patients it serves. Factors that influence quality of life are highly individualized, encompassing social, economic, or cultural determinants of health. In particular, cultural determinants remain an understudied element of palliative care. Objectives: The purpose of this article is to identify key concepts and issues arising from offering culturally relevant palliative care by reviewing how the concept of culture has been discussed in Canadian palliative care literature. Design: A scoping review of medical databases was conducted to identify recent Canadian literature connecting culture and palliative care provision. This review yielded 21 relevant results from the past 10 years. Results: Ideas frequently mentioned in Canadian palliative care literature include cultural competency in health care providers, cultural sensitivity of treatment options, and cultural accessibility of available services. Issues that arose from the literature included differing ideas of the meanings of life and death, visibility of cultural minority groups, spiritual care needs, desire to involve friends and family in care, and misunderstandings of language and communication styles. Conclusion: The results of this review provide a starting point from which health care providers can begin lending attention to cultural determinants of health, thus improving palliative care services for diverse populations.